Connecting Internal Communication and Employee Engagement in Organisation: A Systematic Literature Review - Nadales Gallego, Alejandra; Galindo-Reyes, Fuensanta Carmen; Garrido-Moreno, Aurora (Sage, 2025)
In recent years, there has been a growing interest in employee engagement in the literature. This study presents a systematic literature review to synthesise existing research linking employee engagement and internal communication. The examined set, comprising 55 papers, is selected using the PRISMA method. The paper identifies current trends, topics, the most relevant authors and journals, and explores geographical distribution and collaboration networks among authors. This is achieved through data and content visualisation using VOSviewer, which enables scientific mapping. Three main thematic clusters emerge: employee engagement, internal communication, and job satisfaction. The findings of this review provide valuable insights for both academic and professional contexts, extending knowledge on the topic and highlighting emerging lines of research.
Keywords: Satisfacción en el trabajo; Comunicación en la gestión; Employee engagement; Internal communication; Job satisfaction; Leadership; Systematic literature review